2018
DOI: 10.3390/buildings8060080
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Virtual Information Modeling Acceptance Based on Project Management Knowledge Areas

Abstract: In the contemporary construction management, poor project performance, cost overrun, and low-quality construction have become a central point of attention for improving project performance including information, interaction and communication management. Virtual design and building information modeling play indispensable role in improving the project performance. The aim of this study is to investigate the benefits and challenges of Virtual Information Modeling as a novel information and communication technolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the information flow phase, lean methods can be helpful for waste reduction within the VDC process. VDC enables the implementation of lean principles and incorporates management for waste elimination, costs reduction, productivity improvement, and projects' positive results creation [77]. Figure 10.…”
Section: Theme I: Lean and Bim Interactionmentioning
confidence: 99%
“…In the information flow phase, lean methods can be helpful for waste reduction within the VDC process. VDC enables the implementation of lean principles and incorporates management for waste elimination, costs reduction, productivity improvement, and projects' positive results creation [77]. Figure 10.…”
Section: Theme I: Lean and Bim Interactionmentioning
confidence: 99%
“…Virtual information modelling (VIM) is a combination of virtual design, construction, and BIM concepts. Didehvar et al, (2018) investigated the benefits and challenges of VIM as a novel information and communication technology method for project management in the Iran construction industry. The author found that VIM had the most significant impact on project integration management, offering both substantial benefits and challenges.…”
Section: Augmented Reality (Ar) Virtual Reality (Vr) Mixed Reality (M...mentioning
confidence: 99%
“…Training, maintenance, and operational costs (Goodrum et al, 2011) are other cost-related barriers. Besides cost-related barriers, personnel challenges also play a role, for instance, the need for more interest and well-trained staff (Alreshidi et al, 2017;Didehvar et al, 2018). Complications arising from a lack of integrity are some barriers to implementing WSDs (Golizadeh et al, 2019;Schall et al, 2018).…”
Section: Barriers To Wsds Adoptionmentioning
confidence: 99%
“…Complications arising from a lack of integrity are some barriers to implementing WSDs (Golizadeh et al, 2019;Schall et al, 2018). Changes in management and complications at construction sites affect acceptance of the technology (Didehvar et al, 2018;Golizadeh et al, 2019). Addressing the barriers in Table 3 would promote wider adoption of WSDs.…”
Section: Barriers To Wsds Adoptionmentioning
confidence: 99%